ANALISA DEBIT BANJIR SUNGAI BONAI KABUPATEN ROKAN HULU MENGGUNAKAN PENDEKATAN HIDROGRAF SATUAN NAKAYASU - S.H Hasibuan (Jurnal APTEK, 2012)
The aims of this research was analyze flood design discharge at Bonai River, Kunto Darussalam Residence, Rokan Hulu District. Method was used used to analyze synthetic unit hydrograph of Nakayasu by rainfall in Pasar Kampar Station at year 2000 to 2009 . The result of this research prove that flood design discharge at Bonai River, Kunto Darussalam Residence, Rokan Hulu District using synthetic unit hydrograph of Nakayasu for return period 50 years is 286.75 m3/s .